Comprehensive evaluation of emulsifying and foaming properties of Gleditsia caspica seed galactomannan as a new source of hydrocolloid: Effect of extraction method. (October 2022) - Niknam, Rasoul; Mousavi, Mohammad; Kiani, Hossein
Abstract: The effect of different extraction methods (aqueous, ultrasound-assisted and microwave-assisted extractions) on the emulsifying and foaming aspects of galactomannan obtained from Gleditsia caspica seed as a newly introduced galactomannan was comprehensively investigated in current research. By increasing galactomannan concentration and utilizing ultrasound or microwave in extraction process, the emulsifying capacity, emulsifying stability, zeta potential and foaming stability were remarkably elevated. On the other hand, the values of foaming capacity, z-average, PDI were diminished. Various parameters including the M/G ratio, molecular weight, viscosity, protein content in galactomannan structure and hydrophilic or hydrophobic nature affect the emulsifying and foaming features. By using ultrasound or microwave, the ability of galactomannan in diminishing surface tension was decreased from 83.11 mN/m (for air/water interface) to 54.17, 50.54 and 52.14 mN/m for samples extracted with aqueous, ultrasound and microwave assisted methods. Graphical abstract: Image 1 Highlights: Emulsifying and foaming aspects of Gleditsia caspica seed galactomannan were comprehensively investigated. The effect of extraction methods on the emulsifying and foaming aspects of mentioned galactomannan was evaluated. By increasing galactomannan concentration and utilizing ultrasound or microwave in extraction process, the emulsifying capacity, emulsifying stability, zeta potential and foaming stability were remarkably elevated.